Uniportal video-assisted thoracic surgery for left upper lobe: single-direction lobectomy with systematic lymphadenectomy - Feng, Mingxiang; Lin, Miao; Shen, Yaxin; Wang, Hao (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
A 62-year-old female was admitted to our hospital after computed tomography (CT) revealed a 2.5 cm × 2.1 cm mass in the left upper lobe. PET/CT scan diagnosed as malignant lesion with no signs of metastasis. Under general anesthesia, the patient was placed in right lateral decubitus position. A 4cm incision was made in the 4th intercostal space with plastic protector. The camera was placed in the upper part of the incision and the instruments were inserted below the camera. Left upper lobectomy along with systematic lymphadenectomy was performed. Total surgical time was 135 min and estimated blood loss was 70 mL. The chest tube was removed on the 2nd postoperative day and the patient was discharged on the 3rd postoperative day with no complication. This uniportal VATS single-direction lobectomy for the left upper lobe is feasible and amplifies the concept of thoracotomy-like minimally invasive surgery.